EVALUASI TORSIONAL PROPERTIES ELEMEN STRUKTUR TEKAN DENGAN BERBAGAI BENTUK DAN UKURAN PROFIL BAJA - Damanik, Almerinda Regina Puspa Sari (JURNAL SPEKTRAN; Vol 13 No 1 (2025), 2025)
Steel structure analysis must be carried out to avoid structural failure when supporting external loads, by checking the limits of the structural capacity. Steel columns are the main structural elements that resist axial compressive forces, whose capacity is depend on the size and shape of the steel profile. Large axial compressive forces can cause steel columns to bend or buckle. The buckling phenomenon can cause the steel column to rotate and twist about the longitudinal axis or cross-sectional axis, this called as torsional buckling. Therefore, it is necessary to evaluate how the shape and size of the cross section determine the capacity of the steel column to resist torsional buckling based on its torsional properties. The evaluation was carried out by examining various standard sizes and shapes of steel profiles, determining cross-section information such as cross-sectional area, calculating the torsional properties of the cross-section, and evaluating the effect of shape and size of steel profile on its torsional properties. The results of the data presentation and calculations are summarized in tables and the determination of their relationship is presented in the description of the analysis and evaluation results. The results show that the most effective cross-sectional shapes to resist torsional buckling are IWF and Channel cross-sections, due to the large values of torsional constants and twisting constants, while the T-section and Single Angle only have torsional constant values, but lack of twisting constant values. This affects the capacity of the cross section to resist the torsional buckling. In addition, the dimension of the flange, web, and the thickness of the larger profile also directly affect the values of the torsional constant and twisting constant.